Світосприйняття східних слов’ян: релігієзнавчий контекст - Соломаха, Ірина; Solomakha, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2013)
Висвітлено особливості світосприйняття східних слов’ян як структурованої, світоглядної системи, у якій закладаються принципи трепетного ставлення до людського життя, до всього довкілля, де людина повинна прагнути до співіснування, співжиття з усім створеним живим і неживим. Features of worldview of eastern Slavs as structured, ideological system in which the principles laid reverent attitude to human life, to the environment. Investigated myth-ritual orientation of Ukrainian incantation, their universalism as a kind of cultural codes that appear in their formal and semantic aspects. Study of outlook guidelines considered as a specific irrational knowledge inherent internal logic, which from the standpoint of rational thinking can normalize as illogical connections that reflect the presence of faith ratio. Attention is focused on the importance of ideological basis of eastern Slavs for contemporaries as a man with one hand, has a duty and responsibility to all life on the other − should strive for coexistence with all living and nonliving created.
Worldview of Eastern Slavs: Religious Context
Keywords: світосприйняття східних слов’ян; outlook eastern Slavs; слова-коди; speech codes; замовляння; charms; збереження життя; saving lives